New data on Soviet catches of blue (Balaenoptera musculus) and right whales (Eubalaena japonica) in the North Pacific - Ivashchenko, Yulia; Clapham, Phillip; Brownell Jr., Robert (J. Cetacean Res. Manage., 2023)
Details are provided on 17 previously unreported catches of blue whales, and 93 catches of North Pacific right whales, all taken illegally by the former USSR. The blue whale catches were made between mid-July and mid-September 1972 in the eastern North Pacific at distances of from 96 to 626 nautical miles from the US west coast (Oregon and Washington); they highlight the inadequacy of the International Observer Scheme, as implemented in 1972, to report or detect illegal whaling. These previously unknown blue whale catches bring the Soviet total to 1,638 for the period 1948–1972. The 93 right whale catches were made during the period 1951–62 around the Kuril Islands, which brings the known total of takes of this species from 1935–1971 to 775 (including 10 taken for scientific research and officially reported at the time).